Bibliometric Analysis of Studies on Social Welfare in Multicultural Societies - Judijanto, Loso; Arisanti, Ivon; Sani, Hasrul (The Eastasouth Journal of Social Science and Humanities, 2025)
This study conducts a bibliometric analysis of research on social welfare in multicultural societies, examining publication trends, key themes, and collaborative networks. Using data from Scopus and analyzed through VOSviewer, the study identifies major research clusters centered on migration, cultural diversity, government policies, and socioeconomic factors. Findings indicate a shift in scholarly focus from economic disparities and human rights to emerging concerns around digital transformation, social integration, and inclusive welfare policies. The study also highlights regional disparities in research contributions, with Western scholars dominating the discourse while emerging research networks develop in Asia and other regions. Additionally, gaps in comparative welfare studies, the role of non-state actors, and the impact of digital technologies on welfare provision are identified as future research priorities. These findings offer valuable insights for policymakers, researchers, and practitioners seeking to enhance welfare policies in diverse and evolving social contexts.